MAPPING THE RISK OF FOREST FIRES IN THE SOUK AHRAS MOUNTAINS - Gouachi Zakia; Tatar Hafiza (International Journal of Innovative Technologies in Social Science, 2024)
Forests fire is the most devastating factor of degradation of the Algerian forest, despite numerous efforts to limit it. Traditional fire prevention and firefighting methods have shown their limitations due to their slowness… , is it therefore useful to adopt new techniques in order to react quickly and effectively. The main objective of this study is to model the «forest fire» risk, in order to produce a risk map, which is indispensable for preventing and informing on fire-vulnerable areas. To achieve this objective, a forest fire risk map was elaborated, on the basis of the scientific methods using geographical information systems and satellite imagery. The adopted approach is an empirical model, involving three parameters controlling the behavior of fire, the topo-morphology of the ground, the combustibility of the vegetation cover and human activity. The study area chosen is one of the most affected areas by this phenomenon (Souk Ahras Mountains). It belongs to the densest forest in Algeria, known for its sensitivity to fire, particularly in relation to its physical conditions (nature of the vegetation cover, climatic conditions (strong Sirocco wind) and socio-economic conditions (high population density).